2021
DOI: 10.1021/acs.analchem.0c05406
|View full text |Cite
|
Sign up to set email alerts
|

Optical Trapping–Polarized Raman Microspectroscopy of Single Ethanol Aerosol Microdroplets: Droplet Size Effects on Rotational Relaxation Time and Viscosity

Abstract: Optical trapping–polarized Raman microspectroscopy of single ethanol (EtOH) microdroplets with a diameter (d) of 6.1–16.5 μm levitated in an EtOH vapor-saturated air/N2 gas atmosphere has been explored to elucidate the vibrational and rotational motions of EtOH in the droplets at 22.0 °C. The Raman spectral bandwidth of the C–C stretching vibrational mode observed for an aerosol EtOH microdroplet was narrower than that of bulk EtOH, suggesting that the vibrational/rotational motions of EtOH in the aerosol syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, ethanol molecules partition to the spherical droplet surface in a Langmuir-type trend. This discrepancy in interfacial partitioning may be caused by a large pressure gradient across the radius of the droplet produced by its highly curved surface. Thus, the mobility of ethanol molecules in nanodroplets may be much lower than that of the planar analogue, resulting in a decreased interfacial partitioning. It is possible that this increased pressure along with the lessened availability of analyte molecules inhibits formation of a cancelling secondary monolayer.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, ethanol molecules partition to the spherical droplet surface in a Langmuir-type trend. This discrepancy in interfacial partitioning may be caused by a large pressure gradient across the radius of the droplet produced by its highly curved surface. Thus, the mobility of ethanol molecules in nanodroplets may be much lower than that of the planar analogue, resulting in a decreased interfacial partitioning. It is possible that this increased pressure along with the lessened availability of analyte molecules inhibits formation of a cancelling secondary monolayer.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical pathways of aerosols have a complicated interplay with the physicochemical properties of aerosols, which could be affected by the chemical composition of aerosols. Atmospheric aerosols usually contain both inorganic and organic species, , which determine the ionic strength and viscosity of aerosols, respectively. These two physicochemical properties have been recognized to play key roles in the reaction kinetics of aerosols. ,, A high ionic strength in aerosols can enhance the reactive uptakes of gaseous reactants, the reaction rate coefficients in aerosol bulks, and the rates of aqueous photolysis. Several recent studies also found that high ionic strengths can enhance the reactive uptakes of SO 2 by peroxides and the sulfate formations from the subsequent SO 2 oxidation in deliquesced aerosol particles. , Conversely, a high viscosity in organic aerosols can lead to slow diffusion times of molecular species and thus the prolonged time scales of dynamic processes in aerosols, while the relationship between viscosity and diffusivity could also highly depend on phase states of aerosols and molecular interactions. , …”
Section: Introductionmentioning
confidence: 99%
“…24,25 Conversely, a high viscosity in organic aerosols can lead to slow diffusion times of molecular species and thus the prolonged timescales of dynamic processes in aerosols, while the relationship between viscosity and diffusivity could also highly depend on phase states of aerosols and molecular interactions. 19,[26][27][28][29][30] The roles of chemical composition in the heterogeneous reaction kinetics of aerosols are often rationalized in terms of the effects of ionic strength and diffusivity to reactions in aerosol bulks. However, for the reactions at aerosol surfaces or interfaces, it still requires more advanced investigations to clarify the potential role of chemical composition.…”
Section: Introductionmentioning
confidence: 99%